High rate of transplacental infection and transmission of Neospora caninum following experimental challenge of cattle at day 210 of gestation - Benavides-Silván, Julio (2012)
In order to investigate the pathogenesis of neosporosis following a primary infection in late pregnancy, cattle were subcutaneously challenged with 5 × 108 Neospora caninum (NC1 isolate) tachyzoites at day 210 of gestation and serial necropsies were then carried out at 14, 28, 42 and 56 days post-infection (dpi). No abortions occurred and all the foetuses were viable at the time of euthanasia. There was a high rate of vertical transmission, as parasites were detected by immunohistochemical labelling and PCR in all the foetuses from 28 dpi. Focal necrotic lesions were observed in the placentomes of the placenta from 28 dpi and showed resolution during later time points, denoted by infiltration of inflammatory cells at 42 dpi and fibrosis at 56 dpi. Foetuses at 28 and 42 dpi showed scarce and isolated lesions which are unlikely to represent a threat to foetal viability. No lesions were observed in the foetuses at 14 or 56 dpi suggesting control of the infection and resolution of the lesions by maternal and foetal immune responses. Once infection was established, it could not be cleared from the host and vertical transmission of the parasite occurred in all infected hosts. Parasite was detected in the placenta at 28 dpi, while in previous experimental infections of cattle at day 70 and 140 of gestation using the same challenge model, it was already present at day 14 post infection. This suggests that a change in the maternal immune response plays a crucial role in limiting the initial infection during the last term of pregnancy.